Respuesta :

Answer:

x=0 and x=4

Step-by-step explanation:

x²-4x=0

x(x-4)=0

make at least one of the x equal 0, so x=0 and x=4

[tex]x {}^{2} - 4x = 0[/tex]

Step 1: Factorise the equation.

Step 1: Factorise the equation.Since x is the only common factor, you'll have

[tex]x( x - 4) = 0[/tex]

Step 2: Since the product of the two equations, i.e. x and x-4, is 0 it means that one equation is zero. The next step is to separate the two equations.

[tex]x = 0[/tex]

[tex]x - 4 = 0 \\ x = 4[/tex]

Note that in the second equation, i.e. x-4, the 4 crosses over to the other side of the equality sign to leave the variable x alone.

[tex]therefore \: when \: \\ x {}^{2} - 4x = 0 \\ x \: will \: be \: equal \: to \: {0 \: and \: 4}[/tex]